Application Of The Novel "Emeritus" Air Cooled Condenser In Geothermal ORC. (September 2017) - Astolfi, M.; La Diega, L. Noto; Romano, M.C.; Merlo, U.; Filippini, S.; Macchi, E.
Abstract: The present work aims to investigate the potential advantages in using a novel wet and dry configuration for heat rejection units in ORC power plants. The reference case is a geothermal power plant that exploits a medium temperature brine and uses a closed loop of cooling water to release the condensation heat. In the calculations, the off-design operation of the whole plant is optimized by a techno-economic point of view with a realistic part-load behaviour for the ORC and the use of experimentally validated correlations for the heat rejection section. The performance attainable with the novel LU-VE Emeritus ® unit equipped with a water spray system and adiabatic panels is compared with those achievable with the same unit in dry operation. Final results show a marked increase of revenues with Emeritus ® units with respect to a dry unit.